2012
DOI: 10.1128/jvi.07217-12
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interactions between Bombyx mori Nucleopolyhedrovirus and Its Host Cells Revealed by Transcriptome Analysis

Abstract: Although microarray and expressed sequence tag (EST)-based approaches have been used to profile gene expression during baculovirus infection, the response of host genes to baculovirus infection and the interaction between baculovirus and its host remain largely unknown. To determine the host response to Bombyx mori nucleopolyhedrovirus infection and the dynamic interaction between the virus and its host, eight digital gene expression libraries were examined in a Bm5 cell line before infection and at 1.5, 3, 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
76
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 63 publications
11
76
0
2
Order By: Relevance
“…In addition, prior studies showed that AcMNPV-infected Sf9 cells have an increased metabolic flux through the tricarboxylic acid (TCA) cycle (46). Thus, results from transcriptome studies of AcMNPV-infected T. ni cells confirm that cellular energy/metabolism pathways are modified during the baculovirus AcMNPV infection (45)(46)(47)(48)(49), and here we document the effects on the regulation of transcripts from these pathways. Prior studies have also shown that supplementing the culture medium of Sf9 cells with glutamine, pyruvate, or alpha-ketoglutarate can increase the yield of baculovirus-expressed proteins and budded virus (47,49).…”
Section: Assembly and Annotation Of The T Ni Tnms42 Transcriptomesupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, prior studies showed that AcMNPV-infected Sf9 cells have an increased metabolic flux through the tricarboxylic acid (TCA) cycle (46). Thus, results from transcriptome studies of AcMNPV-infected T. ni cells confirm that cellular energy/metabolism pathways are modified during the baculovirus AcMNPV infection (45)(46)(47)(48)(49), and here we document the effects on the regulation of transcripts from these pathways. Prior studies have also shown that supplementing the culture medium of Sf9 cells with glutamine, pyruvate, or alpha-ketoglutarate can increase the yield of baculovirus-expressed proteins and budded virus (47,49).…”
Section: Assembly and Annotation Of The T Ni Tnms42 Transcriptomesupporting
confidence: 61%
“…In the highly upregulated or induced unigenes, we also noted that several genes encode proteins associated with mitochondria and energy/metabolism, such as cytochrome oxidase subunit III (UN068092), NADH dehydrogenase subunit 2 (UN067842), and ATP synthase F0 (UN067090). Xue et al (45) also identified host genes related to the mitochondrial respiration pathway as highly upregulated over the course of Bombyx mori NPV (BmNPV) infection of B. mori Bm5 cells (45). In addition, prior studies showed that AcMNPV-infected Sf9 cells have an increased metabolic flux through the tricarboxylic acid (TCA) cycle (46).…”
Section: Assembly and Annotation Of The T Ni Tnms42 Transcriptomementioning
confidence: 99%
“…Several prior studies of AcMNPV transcriptomes have been performed with microarrays and by real-time PCR analysis, although data are often difficult to interpret in light of the inherent problems associated with the tightly packed AcMNPV genome and overlapping transcripts (31)(32)(33). Recently, the Bombyx mori NPV (BmNPV) transcriptome was examined using RNA-Seq, and Illumina reads were mapped to a reference transcriptome database (34). However, the issue of extensive overlapping transcripts and antisense transcripts was not specifically addressed and therefore remains largely unresolved.…”
mentioning
confidence: 99%
“…In vAchrf-1-infected Ld652Y cells, the levels of both full-length and cleaved Ld-Dronc decreased gradually from 24 to 120 h postinfection (Fig. 4B), likely due either to apoptosis induction late in the infection cycle (51,53) or to the shutdown of host protein synthesis, which is often observed during progeny virus replication (54)(55)(56). In contrast, cleaved Ld-Dronc corresponding to prodomain and p20 domain was not detected in LdMNPV-infected Ld652Y cells (Fig.…”
Section: Resultsmentioning
confidence: 89%